PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Sukrada, I Ketut; Merawati, Luh Komang; Arizona, I Putu Edy (Jurnal Riset Akuntansi (JUARA), 2019)
This study aims to examine the effect of financial ratios on stock returns with Corporatesocial responsibility as an intervening variable in manufacturing companies listed on the IndonesiaStock Exchange in 2015 - 2017. The population of this study includes 156 manufacturingcompanies in the Indonesia Stock Exchange with purposive sampling techniques obtained 52companies with a research period of 2015 - 2017. Data analysis methods used are path analysis.Based on the results of data analysis, it shows that; (1) financial ratios have a positiveeffect on stock returns; (2) corporate social responsibility is not an intervening variable the influenceof financial ratios on stock returns.